EFFECT OF RICE HULL IN THE DRIED HOTEL FOOD WASTE BASED-DIET ON LIPID CHARACTERISTICS AND MEAT QUALITY OF BARROWS - Purnamartha, I.M.; Setiyono, S.; Panjono, P. (Journal of the Indonesian Tropical Animal Agriculture, 2013)
The study was constructed to observe the effect of rice hull as a fiber sources in the dried hotelfood waste based-diet on fat and cholesterol level of pork. Twenty four heads of two months old ofLandrace x Yorkshire cross barrows were randomly divided into four treatment groups, i.e. without ricehull (R0), 10% rice hull (R1), 20% rice hull (R2), and 30% rice hull (R3). They placed in individualconcrete pen with 1.9 m in length and 0.5 m in width. Feed and water were given as ad libitum.Observation was done for 10 weeks prior to slaughter. Completely Randomized Design was used in thisstudy. Data obtained was analyzev by anova and mean comparison of Duncan's new Multiple RangeTest. Fat content of R0, R1, R2, dan R3 pork were 14.09±0.31, 13.30±0.44, 12.9±20.30 and11.95±0.56%, respectively. Fat content of pork of R0 was higher (P<0.05) than that of others groups.Cholesterol content of pork of R0, R1, R2 and R3 were 256.47±30.23, 252.34±26.56, 217.63±21.93 and199.21±25.94 mg/100 g, respectively. Cholesterol content of pork of R3 were lower (P<0.05) than thoseof R0. It is concluded that the use of rice hull up to 30% in the dried hotel food waste based-diet candecreases fat and cholesterol levels of pork.